Análise das estruturas interativas em jogos multiplayer: caso Counter-Strike - Vicente, Victor Emmanuel José de Sousa (2005)
The present inquiry presents a proposal of analyzes of the interactive structures in games carried through in digital environments and its possible reuse in new communication processes in cooperation with the computer sciences and the hypermedia. It currently analyzes the processes of authoring of games of the historical, conceptual point of view and the perspectives of interdisciplinary concept gifts inside of the research carried through in the academy in that it says respect the matrices of the language and thought. The referencial model multi-player (Counter-Strike) studied involves strategies of complex reuses and interactive. The research identified as basic elements of the process the work in qualified teams, either in the planning, same development and in the conduction of the practical ones of use to the user level. The used concept of team is of interdisciplinary concept, what it becomes the interesting research for the contexts of the entertainment and education. The reuses concept if becomes operative when it is developed by the current inquiries on the interactive, which is presented from the research in semiotics and hypermedia, leaving the open possibility of its extension for the area of the education.